2009
DOI: 10.1007/s00595-008-3982-5
|View full text |Cite
|
Sign up to set email alerts
|

Vacuum-assisted closure and bilateral pectoralis muscle flaps for different stages of mediastinitis after cardiac surgery

Abstract: Early BPMMF is an effective surgical treatment for DSWI in patients with an unstable sternum and osteomyelitis. VAC may be considered for patients without osteomyelitis but a stable sternum, or as adjuvant therapy in patients with comorbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
2
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(48 citation statements)
references
References 26 publications
1
39
2
6
Order By: Relevance
“…Results showed that VAC reduced the risk of deep infection by almost 80% when compared to conventional dressing [19]. In agreement with this study, studies and case reports of osteomyelitis treated with negative pressure increased granulation tissue formation, decreased number of reconstructive procedures and have variably affected bacterial burden [5,11,20]. With this in mind, the VAC system was chosen to treat the patient in this report.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Results showed that VAC reduced the risk of deep infection by almost 80% when compared to conventional dressing [19]. In agreement with this study, studies and case reports of osteomyelitis treated with negative pressure increased granulation tissue formation, decreased number of reconstructive procedures and have variably affected bacterial burden [5,11,20]. With this in mind, the VAC system was chosen to treat the patient in this report.…”
Section: Discussionsupporting
confidence: 78%
“…Donor muscle selection is based on the dimensions of the defect and function or purpose of the reconstructive procedure and can be harvested alone or as a composite flap (skin and muscle) [2][3][4]. Muscle flaps augment vascular supply of compromised wounds by inducing angiogenesis, which is used for the management of chronic osteomyelitis, shearing wounds to the distal extremities, decubital ulcers, and ablative oncological procedures [3][4][5]. The increased blood supply through transferred muscle enhances the host defense mechanism to a compromised wound by increasing local concentrations of immunoglobulins, complement, neutrophils, and oxygen tension [2,6].…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6] The DSWI causes necrosis and breakdown of the sternum, rendering the vital organs in the thoracic cavity vulnerable; therefore, it is of utmost importance to achieve fast healing of the defect. During the past decade, there has been a trend toward using topical negative pressure (TNP) therapy to aid the healing process before rewiring the defect.…”
mentioning
confidence: 99%
“…It is applied on chronic to acute wounds, such as pressure ulcers, diabetic ulcers, problematic surgical wounds, traumatic wounds, and skin grafts [1]. Negativepressure wound therapy is widely applied in the field of thoracic surgery for poststernotomy mediastinitis [2][3][4][5][6], while its use for closure of open-window thoracostomy wounds has recently been attracting attention [7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%